The Role of the Learner in Task-Based Language Teaching: Theory and Research Methods - Mohamed Salah (Studies in Applied Linguistics & TESOL)
This volume, edited by Craig Lambert, Scott Aubrey, and Gavin Bui, presents a collective effort by second language (L2) scholars to explore the role of the learner in Task-Based Language Teaching (TBLT). The volume stems from two colloquia––The Biennial Conference on Task-Based Language Teaching in 2015 at the University of Leuven, Belgium, and The Second Language Research Forum in 2016 at Columbia University, United States––focused on contemporary viewpoints and practices regarding the role of the learner in L2 task performance. It builds on the well-established recognition that affective and conative factors are central in L2 acquisition.